Três ensaios sobre produtividade agrícola - Carvalho, Rosemeiry Melo (2003)
This thesis studies agricultural productivity both from an empirical and theoretical perspective. On the empirical side, a stochastic frontier is estimated for Brazilian states and the Data Envelopment Analysis methodology is employed for South American countries. Regarding the theoretical perspective, the impact of an increase on agricultural productivity upon economic growth and welfare is analyzed by means of an endogenous growth model. We conclude that agricultural productivity plays a major role in determining the growth rate of economies.